Environmental Degradation: Causes and Remediation Strategies 2020
DOI: 10.26832/aesa-2020-edcrs
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Degradation: Causes and Remediation Strategies

Abstract: Today, environmental degradation is the utmost problem leading to the extinction of several living organisms on the earth. Environmental degradation can be seen in the form of lost living forms due to disturbances in the earth's ecosystem. The recent developments in human civilization are the major reason for the degradation of the environment and its quality. This edited book is the compliance of selected reports destined to provide information regarding causes, effects and mitigation strategies of environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 125 publications
0
9
0
Order By: Relevance
“…Although, SARS-CoV-2 may be transmitted in water through human stool, it is still not so clear how long it can survive in groundwater albeit limited researches have suggested that it can survive for weeks in groundwater ( Gundy et al, 2009 ). In addition, waste such as surgical and nose masks, tissue papers, and personal protective equipment (PPE) discharged from hospitals without proper treatment into the water system can also lead to transmission of pathogens such as viruses ( Kumar et al, 2020 ). This suggests that improper solid waste management practices in Africa could be one of the routes of SARS-CoV-2 transmission.…”
Section: Sources and Routes Of Sars-cov-2 In Water Systems In Africamentioning
confidence: 99%
“…Although, SARS-CoV-2 may be transmitted in water through human stool, it is still not so clear how long it can survive in groundwater albeit limited researches have suggested that it can survive for weeks in groundwater ( Gundy et al, 2009 ). In addition, waste such as surgical and nose masks, tissue papers, and personal protective equipment (PPE) discharged from hospitals without proper treatment into the water system can also lead to transmission of pathogens such as viruses ( Kumar et al, 2020 ). This suggests that improper solid waste management practices in Africa could be one of the routes of SARS-CoV-2 transmission.…”
Section: Sources and Routes Of Sars-cov-2 In Water Systems In Africamentioning
confidence: 99%
“…Adsorption of wastewater using silicon oxide is a low-cost, innovative, efficient, and simple technique of removing contaminants from wastewater. Silicon oxide, derived from agricultural waste biomass, is one of the adsorbents utilized in a variety of sectors today [14]. It possesses a suitable pore size distribution, large specific surface area, and strong surface reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with other nanoparticles, the silicon oxide manufacturing technique is very inexpensive, and its regeneration is simple. In recent years, this has led to the development of novel low-cost and efficient adsorbent materials [14,15]. It has been discovered that silicon dioxide derived from different agricultural wastes has a great potential for pollution effluent removal.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical, physical, radioactive waste material, pathogens from industrial effluents, agricultural run-off, domestic sewage, construction activities, and mining activities causes contamination in freshwater and affect the freshwater biodiversity (Richardson et al, 2007). However, 70% to 80% of municipal wastewater is discharged untreated into freshwater bodies and also many industrial activities are known for its responsibility for dumping millions of tons of heavily pollutants such as solvents, heavy metals, toxic sludge every year but the pollution of water does not only affect the water bodies, they also adversely affecting the land, agriculture, aquatic life and human health to a greater manner (Vishwanath et al, 2017;Bassem, 2020;Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%